Study of the Application of the ABC Cost Method in the Mypes of Ecuador - Arellano Cepeda, Otto (2017)
The Micro and Small Enterprises need to implement a cost accounting management system as a basic element that allows the determination of costs of production of goods and services, for decision making and establishing the sales price that allows Compete in the market with your competition. In this context, the objective of the research is to determine the importance of the application of the cost-based method of activities (ABC) in the accounting of costs in the Micro and Small Enterprise of the Republic of Ecuador. For this purpose, a documentary review of the research carried out on accounting and costing in the MyPES was used as methodology. It is causal. The study considers a population of 972,846 and a sample of 22,919 micro enterprises. The results show that the use of cost accounting is related to management accounting; Occurs in manufacturing companies with a higher degree than in commercial and service companies, and it is likely that the ABC method has been applied in the calculation of costs by SMEs.